Masaüstü yayıncılıkta görsel kalite ve görsel algılama kriterleri - Söker, Hülya (My University, 1999)
This study, named the research of the criteria visual quality and perception at desktop press, contains six main sections. As an introduction to the subject, in the first section, information about the factors affecting the subject and tests given to the subjects was given briefly. In the second parts, passing from handwriting to printing press writing was historically explained. Under the light of the description of printing press writing, after typeface had been defined, different classifications of printing press writing were given. In the third section including information about anatomic structure of printing press writing, printing press writing' s features were also defined and analyzed. In the fourth section, after defining type-setting, the frame of this section was formed by detailed information of rules and types of type-setting. These arrangements also covered one part of the tests. Legibility, which is one of biggest problem of typography was analyzed in the fifth section. Meanwhile, readibility was explaned. The factors affecting were researched in a detailed manner. Information about experimental studies which form the basis of this study was given in the sixth section. Beside all these detailed information presented former sections, conclusion section was developed by synthesis of all relevant knowledge and results gathered from the tests applied to the subjects under certain rules which was modified before. The study was enriched by samples and tables found throughout literature review.

Masaüstü yayıncılıkta görsel kalite ve görsel algılama kriterlerinin incelenmesi isimli bu araştırma altı ana bölümden oluşmaktadır. Konuya giriş niteliğindeki birinci bölümde: araştırmada hedeflenen konular ve deneklere uygulanan testlerde hangi faktörlerin incelendiği hakkında kısaca bilgi verildi. İkinci bölümde: el yazılarından baskı yazılarına geçiş tarihsel olarak açıklandı. Baskı yazısının tanımı ışığında karakterin de tanımı yapılarak baskı yazılarının değişik sınıflandırılmasına yer verildi. Baskı yazılarının anatomik yapısı hakkında bilgi içeren üçüncü bölümde: baskı yazılarının özellikleri kapsamlı olarak incelendi ve tanımları yapıldı. Dördüncü bölümde dizginin tanımından sonra bu bölümün içeriği genel dizgi kuralları ve dizgi düzenleme çeşitlerinin detaylı anlatımları ile oluşturuldu. Bu düzenlemeler aynı zamanda testlerin bir bölümünü de kapsadı. Tipografinin en büyük problemlerinden biri olan okunabilirlik kavramı beşinci bölümde analiz edildi. Bunun yanısıra okunurluktan da bahsedildi, okunabilirliği etkileyen faktörler ise detaylı olarak ele alındı. Araştırmanın temelini oluşturan deneysel çalışmalar hakkındaki bilgiler ise altıncı bölümde yer aldı. Daha önceki bölümlerde sunulan tüm bu detaylı bilgilerin yanında ilgili bilgi ve deneklere uygulanan testlerden tespit edilen sonuçların daha önceden varolan bazı kurallar ile birlikte sentez edilmesiyle sonuç bölümü geliştirildi. Bu çalışma, anlatımların dışında baştan sona ele alınan konuların örnek ve tablo gösterimleriyle zenginleştirildi.
Keywords: Masa Üstü Yayıncılık